IPod & iTunes : the missing manual - Biersdorfer, J. D. (Missing manual., 2006)
When Apple introduced the iPod in 2001, CEO Steve Jobs declared, "listening to music will never be the same again." He was right on the money. The iPod grabbed attention right away, and by the end of 2005, more than 41 million of them had sold. iPod is the dominant digital music player on the market, and for the first time, Apple gets to feel like Microsoft. iPod steadily evolved through five generations since then, and today the dynasty ranges from a screenless 512-megabyte version that can hold plenty of songs for your gym routine to a 60-gigabyte multimedia jukebox that can spin out an entire season of "Desperate Housewives", along with thousands of color photos and all that colorful music. An iPod is many things to many people, but it can be much more than most people realize. That's where iPod and iTunes: The Missing Manual comes inches Like the device itself, this book is a long-running bestseller, now in its fourth edition. What makes it so popular is the wealth of useful information it brings to anyone who breaks open iPod's distinctive packaging-especially since Apple doesn't supply a manual of its own. Once again, we've updated this guide to fully explain the ins and outs of iPod, including the nano, the shuffle, and all the latest features and uses, such as: The 5th generation Video iPod, which can hold 15,000 songs, 25,000 photos, and 150 hours of video iTunes 6, where you can buy tunes, subscribe to Podcasts, tune into internet radio, download videos, build playlists, and more Going beyond the music to use iPod as an external drive, an eBook, a personal organizer, a GameBoy, and a slide projector Extreme iPodding with shareware and AppleScripts, using an iPod with external speakers (including the car stereo), accessories, and troubleshooting It's been five years since iPod hit the scene, but, clearly, the evolution has only just begun. iPod and iTunes: The Missing Manual gives you everything you need to evolve with it.